PENGEMBANGAN DAN ANALISIS ERGONOMI KURSI OPERATOR MESIN VULKANISIR BAN DENGAN METODE REVERSE ENGINEERING - Yuni Hermawan (Jurusan Teknik Mesin Fakultas Teknik Universitas Jember, 2011)
The likelihood of complaints occurring in the tire retreading machine operator is very possible especially if the seats are not as ergonomic. This situation occurs and will be redesign chair process machine operators with a method of tire retreading Reverse Engineering (RE) with respect to ergonomic aspects. By analysis using finite element software simulations, we can determine the voltage that occurs in part the concept of tire retreading machine operator seat. So it can be seen clearly the force distribution that occurs in material unit concept tire retreading machine operator seat. To calculate the material strength analysis by finite element software can use the help of CATIA V5R14 software. This is intended to get maximum results and an accurate analysis. After the experiment, the voltage that occurs on a cushion of 1.81x106 N/m2 located on the bottom face of the middle cushion while the minimum working voltage is 1.81x105 N/m2 located on the bottom front cushion edges. The voltage that occurs on a cushion of 1.27x108 N/m2 located at the base of the curved pipe connections while the minimum working voltage is 1.27x107 N/m2 located at the base of a straight pipe connection. Ergonomics analysis obtained by using the method Rula when operators run the machine has the injury risk rate value is 2, which shows the attitude of the body is acceptabel and do not need to be changed for the long term. Keywords: ergonomic, chair operator and reverse engineering